THE IMPACT OF MANAGERIAL OWNERSHIP, SIZE, AND GROWTH RATE ON CAPITAL STRUCTURE - Agus Munandar (JURNAL RISET TERAPAN AKUNTANSI, 2017)
This paper examines the influence of managerial ownership, size, and growth rate on capital structure of companies which were belonged to Consumer Goods Industry and Miscellaneous Industry listed inIndonesia Stock Exchange (IDX) on the year period 2009 -2014. Panel data regression analysis is used to investigate the influence of independent variables on firm’s capital structure. The empirical results demonstrate the capital structure (proxied by the total debt ratio) of the companies is positively determined by their size (proxied by the total revenue). The results of the analysis also showed that capital structure is also negatively determined by managerial ownership (measured by comparing themanagerial share ownership with total of circulated shares). The finding also show that leveragenegatively determined by their growth rate (proxied by the asset growth rate). These findings are consistent with the previous literature.